Xylaria iriomotensis sp. nov. from termite nests and notes on X. angulosa - Izumi Okane; Huei-Mei Hsieh; Yu-Ming Ju; Chun-Ru Lin; Chun-Yun Huang; I-Ching Kuan (Botanical Studies)
Abstract Background Fungus gardens of the termite Odontotermes formosanus, excavated from Iriomote Island, Okinawa Prefecture, Japan, were subsequently incubated under laboratory conditions. A Xylaria species emerging from these fungus gardens was initially identified as X. angulosa, a species originally described from North Sulawesi, Indonesia. The Iriomote fungus is now described as a distinct species, X. iriomotensis. Results Xylaria iriomotensis is peculiar in producing the teleomorph in culture but lacking an anamorph. Cultures of X. angulosa were obtained from two Taiwan specimens, which agree with the holotype from BO and the isotypes from NY and WSP in their stromata being repeatedly dichotomously branched and possessing a black core. In contrast to X. iriomotensis, X. angulosa does not form the teleomorph in culture but a typical Xylaria anamorph with conidiophores densely arranged in palisades. The ITS sequence obtained from the WSP isotype shared high similarities with those two Taiwan specimens as well as an Indian specimen, reconfirming the latter three specimens as X. angulosa. These four specimens shared 98.28–99.66% similarities at ITS sequences among themselves but only 84.25–85.01% similarities with X. iriomotensis. Molecular phylogenetic studies based on sequences of multiple protein-coding loci indicate that, while X. iriomotensis is grouped with three soil-dwelling species of the X. guepini cluster, X. angulosa belongs to the X. nigripes cluster, which includes all known species capable of producing massive sclerotia. Conclusion Xylaria iriomotensis has the teleomorph known only in culture, remaining to be rediscovered in its natural habitat where the stromatal morphology may be somewhat varied. The geographic distribution of X. angulosa, previously known only in Indonesia, has been expanded to Taiwan and India. Xylaria angulosa grouping with the X. nigripes cluster in our phylogenetic analyses indicates its potential to form massive sclerotia within termite nests.